2002
DOI: 10.1074/jbc.m200197200
|View full text |Cite
|
Sign up to set email alerts
|

Human ING1 Proteins Differentially Regulate Histone Acetylation

Abstract: affects the degree of physical association between proliferating cell nuclear antigen (PCNA) and p300, an association that has been proposed to link DNA repair to chromatin remodeling. Together with the finding that human ING1 proteins bind PCNA in a DNA damagedependent manner, these data suggest that ING1 proteins provide a direct linkage between DNA repair, apoptosis, and chromatin remodeling via multiple HAT⅐ING1⅐PCNA protein complexes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
112
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(119 citation statements)
references
References 36 publications
7
112
0
Order By: Relevance
“…Interestingly, it has been proposed previously that p33 ING1 could play a role in HP1 deposition during formation of nascent constitutive heterochromatin (39). One possible explanation for our observation is linked to the reported ability of p33 ING1 to modulate histone acetylation (7,9,39). There is clear pharmacological and genetic evidence indicating that histone deacetylation is needed for the tethering of HP1 proteins to chromatin (40 -43).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Interestingly, it has been proposed previously that p33 ING1 could play a role in HP1 deposition during formation of nascent constitutive heterochromatin (39). One possible explanation for our observation is linked to the reported ability of p33 ING1 to modulate histone acetylation (7,9,39). There is clear pharmacological and genetic evidence indicating that histone deacetylation is needed for the tethering of HP1 proteins to chromatin (40 -43).…”
Section: Discussionmentioning
confidence: 76%
“…Several ING proteins have been shown to act as upstream regulators of p53 in overexpression experiments, either increasing p53 protein stability (4) or promoting the acetylation of Lys residues at the C terminus of p53 (5,6). The latter effect is likely mediated by the association of ING proteins to acetyltransferases such as CBP/p300 or PCAF (7) or deacetylases such as Sir2 (6). ING proteins also participate in the regulation of chromatin dynamics.…”
mentioning
confidence: 99%
“…Of these interactions, endogenous ING1 and ING2 co-immunoprecipitate CBP and p300, respectively, suggesting that ING1-CBP and ING2-p300 complexes might be present in vivo [Vieyra et al, 2002a;Pedeux et al, 2005]. With respect to ING4-p300/CBP and ING5-p300/CBP interactions, the association was demonstrated via transient overexpression strategies ; whether the endogenous proteins interact physiologically remains to be determined.…”
Section: Chromatin Regulation: Mammalian Ingsmentioning
confidence: 99%
“…ING proteins have been linked functionally to the p53 pathway at different levels, including the control of p53 protein stability, as transcriptional cofactors, or through post-translational modifications of p53 (Nagashima et al, 2001;Nourani et al, 2001;Gozani et al, 2003). ING proteins also participate in chromatin remodelling through their association with histone deacetylases and histone acetyltransferases (Nourani et al, 2001;Feng et al, 2002;Kuzmichev et al, 2002;Vieyra et al, 2002;Xin et al, 2004;Goeman et al, 2005). The most extensively studied member of the ING family is p33ING1, one of the products of the ING1 locus (also referred to as p33ING1b, or ING1b elsewhere; Feng et al, 2002).…”
mentioning
confidence: 99%
“…More importantly, there is ample evidence, both in mammals and yeast, showing that ING proteins can form complexes with histone deacetylases and histone acetyltransferases. Based on this, it has been suggested that ING proteins could play a role in transcriptional control, through chromatin remodelling (Nourani et al, 2001;Skowyra et al, 2001;Feng et al, 2002;Kuzmichev et al, 2002;Vieyra et al, 2002;Xin et al, 2004;Goeman et al, 2005). An increasing number of evidences indicate that ARF can have a direct role in transcriptional control (Kamijo et al, 1998;Rocha et al, 2003Rocha et al, , 2005Calabro et al, 2004;D'Amico et al, 2004;Datta et al, 2004;Kalinichenko et al, 2004;Qi et al, 2004) and, therefore, it is feasible that ARF might cooperate with p33ING1 in transcriptional regulation, through chromatin remodelling processes.…”
mentioning
confidence: 99%